Community and heritage management: Linking stakeholders to archaeological sites in Kichakbadh - Thapa, Abhijeet (Nepalese Culture, 2019)
Community has been much of a striking terminology these days when associated with heritage management. Communities living nearby heritage sites, while at one hand are agents of conservation, on the other hand are sources of destruction in heritage sites and agents of risks. As such, this research unfolds the contested roles of local people for taking ownership of heritage management, understanding heritages, transmitting oral intangible values and valuing destination image at Kichakbadh Province -1, Nepal. The research, aimed at studying heritage management issues around the site has been supplemented by multiple field visits, numerous questionnaires and interviews with locals, visitors and experts. This article chiefly deals with the second phase of author’s exploration carried out on an annual fair called Maghe Purnima at Kichakbadh in 2019. While science of archaeology restricts human activities in conserved places, large fairs are held in archaeologically sensitive areas of Kichakbadh posing threats to archeological wealth there. To utter dismay, archaeological crimes are still common in many sites at Kichakbadh. Multiple field-visits, questionnaire with the stakeholders, visitors and community during the fair reveal that minimal traces of community and state level endeavors to conserve the sites do not meet the vast rescue requirements that Kichakbadh is actually in need of.